Etanercept/celecoxib on improving MRI inflammation of active ankylosing spondylitis: A multicenter, open-label, randomized clinical trial - Tu, Liudan; Zhao, Minjing; Wang, Xiaohong; Kong, Qingcong; Chen, Zena; Wei, Qiujing; Li, Qiuxia; Yu, Qinghong; Ye, Zhizhong; Cao, Shuangyan; Lin, Zhimin; Liao, Zetao; et al. (Frontiers in Immunology, 2022)
Objective To investigate the efficacy and safety of clinical, magnetic resonance imaging (MRI) changes in active ankylosing spondylitis (AS) patients with etanercept and celecoxib alone/combined treatment. Methods A randomized controlled trial was conducted in three medical centers in China. Adult AS patients with BASDAI ≥4 or ASDAS ≥2.1, CRP >6 mg/L, or ESR 28 mm/1st hour were randomly assigned (1:1:1 ratio) to celecoxib 200 mg bid or etanercept 50 mg qw or combined therapy for 52 weeks. The primary outcomes were SPARCC change of the sacroiliac joint (SIJ) and spine and the proportion of patients achieving ASAS20 response at 52 weeks. Results Between September 2014 and January 2016, we randomly assigned 150 patients (mean age, 32.4 years; mean disease duration, 109 months), and 133 (88.6%) completed the study. SPARCC inflammation scores of the SIJ and spine decreased in the three groups, and significant differences were found between the combined group and the celecoxib group [between-group difference: −6.33, 95% CI (−10.56, −2.10) for SIJ; −9.53, 95% CI (−13.73, −5.33) for spine] and between the etanercept group and the celecoxib group [between-group difference: −5.02, 95% CI (−9.29, −0.76) for SIJ; −5.80, 95% CI (−10.04, −1.57) for spine]. The ASAS20 response rates were 44%, 58%, and 84% in the celecoxib, etanercept, and combined groups, respectively, and a significant difference was only found between the combined and the celecoxib groups. Conclusion Etanercept with or without celecoxib decreases inflammation detected by MRI at 1 year compared to celecoxib alone in active AS patients. The combination of etanercept and celecoxib was superior to celecoxib alone for the primary clinical response. Clinical Trial Registration ClinicalTrials.gov, identifier NCT01934933.